Implementasi Program Edukasi Hukum sebagai Langkah Preventif Penyalahgunaan Narkoba di MI Miftahul Ulum, Desa Pulau Mandangin, Kabupaten Sampang - Syaiful Anam; Achmad Taufik; Syaiful Syaiful; Ria Kasanova; Fredy Yunanto; Mohammad Rudiyanto (Lembaga Pengembangan Kinerja Dosen, 2024)
Drug abuse is a significant public health issue in Indonesia, especially in rural areas such as Mandangin Island Village, Sampang Regency. This study aims to evaluate the implementation of a legal education program as a preventive measure for drug abuse at MI Miftahul Ulum. The six-month program involved lectures, interactive discussions, and legal case simulations. The research methodology included data collection through questionnaires, interviews, and observations to assess improvements in students' knowledge and attitudes towards drugs. The results showed that there was a significant increase in students' knowledge regarding the legal aspects of drug abuse, with the average score increasing by 30% after attending the program. Participant responses showed high enthusiasm and a better understanding of the legal consequences. However, challenges such as limited time and resources need to be addressed to improve the effectiveness of the program. Recommendations for improvement include expanding time and resource allocation and integrating the program with other prevention efforts. The program is expected to serve as a model for the implementation of legal education in other educational settings to increase drug awareness and prevention more broadly.